German English-medium linguistics journal abstracts over the last 30 years : Quantitative and qualitative structural developments - Ivanova, Marina (Jan Kochanowski University Press, 2023)
Abstracts are central to academic writing as they summarise and promote publications – this paper shows that the widespread use of abstracts started in the 90s and increased rapidly, becoming a standard. It analyses 593 articles with 555 abstracts from nine linguistics journals, affiliated with the Web of Science to German institutions. The focus is on global rhetorical structures adopted – from introduction/research questions to methods, results, discussions, and conclusions. Additionally, I identify trends in writers’ stance expression through selected metadiscourse features as expressed in subjects and verbs. The analyses demonstrate that abstracts from Germany have become more unified towards the scientific IMRAD model. This model, however, has been adapted to the advertising function of the abstract with a stronger emphasis on the authors’ contributions and article’s importance (especially in introductions, methods, and results) and rare discussions of conclusions and limitations. Thus, general academic writing structures have been adapted to genre-specific functional practices over the last 30 years.